A comprehensive bibliometric and patent landscape of solar desalination: Trends, innovations, and global contributions - Belmehdi Fatima; Othmani Samira; Taha Janan Mourad (E3S Web of Conferences)
The global water scarcity crisis, driven by increasing demand and declining freshwater supplies, necessitates innovative solutions like solar desalination, which uses abundant seawater and solar energy to produce fresh water. This study applies a bibliometric analysis to solar desalination, revealing a sharp rise in publications and patents after 2010. SCOPUS data identifies six main research areas, including “Engineering” and “Environmental Science.” India leads in publications with 1,668, while China dominates patent filings and academic influence. Patent data from PATSNAP shows that 71% of patents are inventions, with 33% still active. Significant innovations include a plasmon-enhanced solar desalination device, as noted in the most cited publication, while solar-driven inter-facial evaporation is emerging. Key patents highlight agile light control for solar desalination and a multi-effect distillation system that optimizes energy use. These breakthroughs not only improve efficiency but also offer adaptable, sustainable solutions to address global water and energy challenges.